(untitled) (International Association of Biologicals and Computational Digest, 2022)
Corals are the tiny invertebrates and are keystone species. The individual colony are called “polyps” which secrete calcium carbonate. Such colony forms a coral reef which play a major role in providing shelter to marine animals. Amongst four major reefs in India one is Gulf of Kachchh. Gujarat has a longest coastline of about 1650 km among all the marine states in India and the Gulf of Kachchh (22⁰15’ - 23⁰40’N; 68⁰20’ - 70⁰40’E) is the biggest gulf along the west coast of India. It is endowed with 42 islands with fringing reef of corals and mangroves which provided congenial habitat to many marine animals (Roy et al., 2015). In the present study, the diversity and distribution of corals were enumerated for three (03) different sites at Poshitra in the Gulf of Kachchh. The study was carried out during December 2019 to March 2020. The method used was random quadrant method. Total 18 hard corals and 01 soft coral were recorded. Further, diversity indices of corals were carried in which site 2 showed highest species richness which is also called alpha diversity, for beta diversity number of species variety were more in site 1 and site 2 and for evenness, the species were more evenly distributed in site 2.